Emotional stimuli candidates for behavioural intervention in the prevention of early childhood caries: a pilot study - Michaela Bartosova; Miroslav Svetlak; Martina Kukletova; Petra Borilova Linhartova; Ladislav Dusek; Lydie Izakovicova Holla (BMC, 2019)
Abstract Background Oral diseases, such as early childhood caries (ECC), have a complex etiology with common, behaviour-related risk factors. Appropriately targeted behavioural intervention using effective tools can help to eliminate risk behaviour leading to ECC. The aim of this study was to ascertain which visual stimuli with a supporting text evoke the strongest emotional response in infants' mothers and, therefore, are suitable candidates for inclusion in behavioural interventions within the prevention of ECC. Methods Thirty-nine mothers of one-year-old children who filled out an originally designed electronic questionnaire, containing 20 visual stimuli with accompanying texts related to dental caries (10/10 with positive/negative intended emotional response), were included in this cross-sectional study. The emotional impact of each stimulus in the mothers was evaluated using the Self-Assessment Manikin (SAM) technique, which represents three emotional dimensions: valence, arousal, and dominance. Results Each of the stimuli was assessed by the mothers of infants based on its emotional impact. The real emotional response (evaluated according to the median of valence) was in line with the primarily intended response in 90% of cases (p < 0.05). The text with a warning evoked a greater emotional response (evaluated according to the median of arousal) in mothers than only the informative instruction (p < 0.05). The relationship between arousal and valence (r = − 0.99; p < 0.05) indicates that the more aversive stimuli raise higher arousal. The significant correlation between valence and dominance shows that the more positive the stimuli, the higher feeling of control over the evoked emotion the mothers have (r = 0.83; p < 0.05), and, on the contrary, the lowest control over emotion is correlated with higher arousal (r = − 0.85; p < 0.05). Generally, mothers rated themselves as in high control of their emotions over the individual stimuli. Conclusions This pilot study proved that negative pictorial and text warnings about the risks of developing caries had the potential to evoke strong emotional responses in the mothers of infants. We identified three visual stimuli that could be included in future extensive motivation material in an attempt to affect the preventive behaviour of mothers, and thus the oral health of their infants.